Noise produced by transverse rumble strips: a case study on rural roadways - Haron, Zaiton; Othman, Mohd Hanifi; Yahya, Khairulzan; Yaacob, Haryati; Hainin, Mohd. Rosli; Mohd Yusof, Mohd Badruddin (2012)
Transverse roadway strips (TRS) are a common approach used by the local authorities in Malaysia for the purpose of road safety on rural roadway. However, there were complaints made by residents about the excessive noise pollution produced by TRS. The objective of this study was to evaluate the external noise produced by the application of TRS, to evaluate and to anticipate the annoyance response due to installation of TRS. The investigations were carried out through the changes of noise level indices, estimation of the annoyance response using the traffic noise index (TNI) and anticipation of resisident response anoyance. Measurements of the external noise level produced by the TRS were taken for two hours at two location with and without TRS. Results showed that TRS increased the equivalent noise level, LAeq1hour, L101hour and L901hour by as much as 14 dB(A), 16 dB(A) and 9 dB(A) respectively. TNI values also increased as much by as 42% and exceeded the suggested value for planning purposes of 74 dB (A) for 3% annoyance from the social surveys. This investigation shows that TRS noise has a very strong impact on the community and this was the reason behind the complaints made by people living in study area.